식용 작물 및 유효 성분을 이용한 면역과민반응에 의한 코 상태 개선 기능성 소재 개발 - 이욱빈 (한국식품과학회, 2024)
Immune hypersensitivity is a growing concern, particularly in relation to allergic rhinitis, which severely affects nasal health. Natural products have emerged as a promising avenue for managing these conditions, offering potential solutions through their bioactive compounds. Recent studies suggest that edible crops and their active ingredients can help alleviate these symptoms by modulating immune responses. This study focuses on functional materials derived from edible crops and their active compounds that have shown effectiveness in improving nasal conditions caused by immune hypersensitivity. Key natural ingredients were evaluated for their ability to regulate immune responses, reduce inflammation, and enhance overall nasal health. Finally, we explore the potential of Lithospermum erythrorhizon in modulating immune hypersensitivity and improving nasal conditions through cytokine balance and mast cell stabilization. This review provides an overview of the potential of these natural functional ingredients as safe and effective long-term solutions for managing immune hypersensitivity.